Book Lists Between Ideologies: Power Games and Canon Changes in Children’s Translated Literature in Poland (1929–1951) - Czernow, Anna; Wieczorkiewicz, Aleksandra (My University, 2025)
Itamar Even-Zohar argues that when new literary models emerge, it is translation that often becomes the means of expanding the literary repertoire, especially in those periods in the history of literature when turning points and moments of crisis occur. This paper addresses two such turning points in the Polish culture: the regaining of independence (1918) and the proclamation of the Polish People's Republic (1945). Juvenile literature of the interwar period was subjected to various ideologizing strategies, the most notable of which was the official one expressed in The List of Books Recommended for School Libraries (1929). After WWII, when the communist ideology was proclaimed, the authorities created another list, namely The Inventory of Books to be Immediately Withdrawn (1951)-the secret document disclosed only afterthe year 2000. Our paper aims to compare these two lists to examine how the collision of ideologies shaped children's translated literature in Poland: which languages dominated the translations; which titles were to be withdrawn after 1951 and which were retained; what reasons may have been underlying the censors' decisions and what impact they had on the canon of juvenile literature; what was the rhetoric of justifications and how to interpret the lists with regard to the canonization techniques. Our research is premised on Pierre Bourdieu's argument about the interdependence between literature and the field of political power.
Keywords: Book lists and canons; Cultural production; Censorship; Polish children’s literature; Politics and ideology; Translations and transfers